2017
DOI: 10.1155/2017/9304592
|View full text |Cite|
|
Sign up to set email alerts
|

The Size Stability of Alginate Beads by Different Ionic Crosslinkers

Abstract: Few studies have discussed the stability of gelled alginate bead size. Therefore, the present study investigated the dynamic shrinkage of gelled alginate beads affected by two common ionic crosslinkers at different concentrations and temperatures. The results indicate that the gelled alginate beads gradually shrank with longer gelling times. The beads incubated in a Ca 2+ solution shrank more dramatically than those incubated in a Ba 2+ solution. Those incubated at room temperature exhibited greater shrinkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Chocolate Bead Size. Manufacturing parameters (nozzle diameter, distance of the nozzle from the gelling solution, temperature, polymer solution feed rate, cross-linking agent concentration) and alginate properties (polymer concentration, molecular weight) can be modified to alter or optimize the geometric properties of the beads [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Chocolate Bead Size. Manufacturing parameters (nozzle diameter, distance of the nozzle from the gelling solution, temperature, polymer solution feed rate, cross-linking agent concentration) and alginate properties (polymer concentration, molecular weight) can be modified to alter or optimize the geometric properties of the beads [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study indicated that alginate beads gelled in Ba +2 solutions were larger than those gelled in Ca +2 solution [20,21]. The microbeads cross linked with Ca +2 (SF6 batch) shrank fastly than remaining curing agents [22]. Based upon pattern of drug release it was clearly understood that drug release is pH dependent.…”
Section: Fig 5: Comparative Dissolution Profile Of Batches From Sf1 mentioning
confidence: 99%
“…Structure resolution can also suffer as a result of imperfect [10] skin [10] osteochondral [11,12] ovarian [13] liver [14] neural [15] high resolution potential for high [22] liver [23] vascular [24,25] pancreatic [26] embryonic [27,28] osteochondral [29] flexibility with printing material viscosity; cross-linking parameters: lack of cross-linking can cause spreading of the structure, whereas over-cross-linking can result in lamination and a failure of the entire structure to coalesce [40,60]. Certain cross-linking methods, such as ionic with alginate, can also cause shrinkage that will affect the intended structure's shape [61]. Bearing this in mind, an ideal bio-ink would have sufficient viscosity not to spread upon deposition, and its cross-linking method would be tightly controlled.…”
Section: (B) Structural Stability and Biodegradabilitymentioning
confidence: 99%